Ultrathin PTAA interlayer in conjunction with azulene derivatives for the fabrication of inverted perovskite solar cells. Issue 41 (7th October 2021) - Tzoganakis, Nikolaos; Feng, Boxu; Loizos, Michalis; Krassas, Miron; Tsikritzis, Dimitris; Zhuang, Xiaodong; Kymakis, Emmanuel
Abstract : A novel π-conjugated azulene molecule as an efficient hole-transport layer in inverted perovskite solar cells is reported. Abstract : Perovskite solar cells (PSCs) have reshaped thin-film photovoltaic technology owning to their exceptionally high power conversion efficiency (PCE) values in conjunction with their low-cost and facile production. PSCs are fabricated following either an inverted or a normal material stacking structure. Inverted PSCs, although they exhibit lower PCE values compared with normal PSCs, show negligible hysteresis, a better stability, and a prolonged lifetime. In this work, novel azulene derivatives, namely Az-4TPA and biAz-4TPA, were synthesized and incorporated in inverted PCEs. These new molecules were extensively characterized and showed good optoelectronic properties. Furthermore, we uncover the relationship between the PCE and the wetting properties of the substrate on which the perovskite layer is grown, demonstrating that a hydrophobic substrate is required. To increase the hydrophobicity of the azulene thin film's surface, PTAA was used. By forming an ultra-thin biAz-4TPA/PTAA bilayer, the optimized devices reached a PCE up to 18.48% and displayed an extended lifetime.